Indirect Monitoring of torc1 Signalling Pathway Reveals Molecular Diversity Among Different Yeast Strains - Martinez-Fernandez, C; Salinas-Sanhueza, F; Molinet-Parada, J; Kessi-Perez, E (John Wiley and Sons Ltd, 2019)
Saccharomyces cerevisiae is the main species responsible for the alcoholic fermentation in wine production. One of the main problems in this process is the deficiency of nitrogen sources in the grape must, which can lead to stuck or sluggish fermentations. Currently, yeast nitrogen consumption and metabolism are under active inquiry, with emphasis on the study of the TORC1 signalling pathway, given its central role responding to nitrogen availability and influencing growth and cell metabolism. However, the mechanism by which different nitrogen sources activates TORC1 is not completely understood. Existing methods to evaluate TORC1 activation by nitrogen sources are time-consuming, making difficult the analyses of large numbers of strains. In this work, a new indirect method for monitoring TORC1 pathway was developed on the basis of the luciferase reporter gene controlled by the promoter region of RPL26A gene, a gene known to be expressed upon TORC1 activation. The method was tested in strains representative of the clean lineages described so far in S. cerevisiae. The activation of the TORC1 pathway by a proline-to-glutamine upshift was indirectly evaluated using our system and the traditional direct methods based on immunoblot (Sch9 and Rps6 phosphorylation). Regardless of the different molecular readouts obtained with both methodologies, the general results showed a wide phenotypic variation between the representative strains analysed. Altogether, this easy-to-use assay opens the possibility to study the molecular basis for the differential TORC1 pathway activation, allowing to interrogate a larger number of strains in the context of nitrogen metabolism phenotypic differences. © 2018 John Wiley & Sons, Ltd.